Bioenergy and global land use change - Pavel Ciaian; d'Artis Kancsz; Miroslava Rajcaniova (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2013)
This is the first paper that estimates the global land use change impact of growth of the bioenergy sector. Applying time-series analytical mechanisms to fuel, biofuel and agricultural commodity prices and production, we estimate the long-rung relationship between energy prices, bioenergy production and the global land use change. Our results suggest that rising energy prices and bioenergy production significantly contribute to the global land use change both through the direct and indirect land use change impact. Globally, the total agricultural area yearly increases by 35578.1 thousand ha due to increasing oil price, and by 12125.1 thousand ha due to increasing biofuel production, which corresponds to 0.73% and 0.25% of the total world-wide agricultural area, respectively. Soya land use change and wheat land use change have the highest elasticities both with respect to oil price and biofuel production. In contrast, non-biomass crops (grassland and rice) have negative land use change elasticities. Region-specific results suggest that South America faces the largest yearly total land use change associated with oil price increase (+10600.7 thousand ha), whereas Asia (+8918.6 thousand ha), South America (+4024.9 thousand ha) and North America (+1311.5 thousand ha) have the largest yearly total land use change associated with increase in biofuel production.
Keywords: C14; C22; C51; D58; Q11; Q13; Q42; 330; Land use change; bioenergy; commodity prices; biofuel support policies